Preferences of Waqf Projects among Indonesians - Mahirani, Aisha Rizqi; Listiana, Lisa (ZISWAF, 2025)
Waqf as an Islamic social finance instrument holds great potential for productive and societal development in Indonesia, given its big size of Muslim population and generous donation behavior. However, the projection of waqf collection which are currently limited to certain form of assets and programs, also creates a gap between the realization and potential of waqf that hinders it full potential. Therefore, this study aims to analyze the programs and characteristics preferred while donating in waqf to fully understand the determinants of waqf interest in each program. This study used a sample of 361 respondents and used multiple regression analysis with stepwise method. The results showed that social waqf is the most popular waqf program compared to social-productive (hybrid) and productive programs. Each program also has its own characteristics which need to be considered to increase the public interest. The results of this study are expected to provide a deeper understanding of the preferences and characteristics of waqf favored by the community, in hope that waqf institutions or nazhir can establish more relevant and effective waqf collection strategies in attracting community participation and achieving broader socio economics objectives.